The relationship between perceived social support and depression in infertile women - Budak, Funda Kavak; Kavak, Mustafa (My University, 2018)
Aim: The purpose of this study is to determine the effect of perceived social support on depression in infertile women.Material and Methods: A cross sectional study. This research was conducted in September 2017 to April 2018 in the infertility center of a university hospital in eastern Turkey. During this period all women who applied to the university hospital’s infertility center were included in this research. The sample size of the study was determined as 102 infertile women using the power analysis. Multidimensional Scale of Perceived Social Support (MSPSS) and Beck Depression Inventory (BDI) were used to collect the data.Results: The mean total MSPSS score of infertile women participating in the study was 63.45 ± 14.35 and the mean depression score was 29.45 ± 14.35. In the study, there was a negative correlation between the total score average of MSPSS and the average score of BDI (p<0.05).Conclusions: In the study, it was determined that the perceived social support by infertile women is high and the depression is low. As the perceived social support by infertile women increases, depression decreases. It may be advisable to provide counseling to nurses to increase their social support for infertile women and to reduce their psychosocial problems.
Keywords: Kadın Hastalıkları ve Doğum; Psikoloji